Analisis Strategi Pemasaran Digital Toya Dayu I’MSD Mengatasi Persaingan Penyewaan Pakaian Adat di Wilayah Perbatasan Negara - Magdalena, Yulita; Atlantika, Yeremia Niaga (Valid: Jurnal Ilmiah, 2024)
The world is entering the modern era which is currently experiencing an all-digital transition. Almost all information and other interests can be obtained through the media, including entrepreneurial activities. The aim of this research is to illustrate the important role of digital-base marketing strategies in the Toya Dayu I’MSD traditional chlothing rental business in overcoming competition in border areas, especially Bengkayang Regency. This research uses descriptive qualitative mothods through observation, interview and documentation stages. The result of this research are: (1) the implementation of digital marketing makes it easier for costumers of obtain business information (2) the streghthening of the digital marketing system needs to be further improved, especially in the media most frequently used by potential consumers (3) increasing the quality and quantity of products/services can increase turnover. With this research, it is hoped that business actors will be more motivated to utilize digital media so that traditional and cultural preservation activities can be carried out optimally usingexisting digital media.